Awareness of HIV/AIDS among transportation staff linked to Dharan municipality, Sunsari, Nepal (Health Renaissance, 2017)
Background: Transportation workers are the high risk group for HIV/AIDS infection because they travel frequently; often engage in unsafe sex to reduce their loneliness. The UN predicts 68 million more deaths over the next twenty years if efforts on prevention are not increased.Objective: To assess the level of awareness and to find out association between awareness about HIV/AIDS and selected variables.  Method: Cross sectional, descriptive study with sample of 197 staff (driver, conductor and helper) of buses and trucks of Dharan city. Purposive sampling technique was used with pretested semi structured questionnaire.Result: The median age of drivers was 28.5, conductor’s 28 and helper’s 21 years. Most of them (84.2%) were within the age group of 15-34 years. Majority stays (77.2%) less than a week away from home. Almost 93% had heard about HIV/AIDS. Still 55.8% & 32.5% believed HIV is transmitted by insect bite and having food together respectively. Eighty one percent believed that HIV/AIDS status of self should not be kept secret with sexual partner. More than (56.7%) had first sexual exposure at the age of 19 or below. Maximum (77.4%) had not used condom at first sexual intercourse. About 15.2% has sex with CSWs. Among them 93.3% were frequenting CSW for more than once. Forty percent had multi-partner.Conclusion: Staff of bus & truck of Dharan showed as the awareness level increased, risk taking behavior decreased and attitude became more positive among the transportation staff. Health Renaissance 2015;13 (3): 82-94